Assessment of Sep1virus interaction with stationary cultures by transcriptional and flow cytometry studies. Issue 10 (28th July 2018) - Melo, Luís D R; França, Angela; Brandão, Ana; Sillankorva, Sanna; Cerca, Nuno; Azeredo, Joana
ABSTRACT: The majority of phage infection studies are performed in bacteria that are growing exponentially, although in nature, phages usually interact also with non-replicating cells. These stationary-phase cells differ from exponential cells morphologically, physiologically and metabolically. The interaction of a Sep1virus with Staphylococcus epidermidis stationary and exponential phase cells was explored. Phage SEP1 efficiently infected both cell culture states, without the addition of any fresh nutrients to stationary cultures. Phage–host interactions, analysed by flow cytometry, showed stationary-phase cells response to phage immediately after SEP1 addition. Quantitative PCR experiments corroborate that phage genes are expressed within 5 min of contact with stationary phase cells. The increase of host RNA polymerase transcripts in stationary cells suggests that SEP1 infection leads to the upregulation of host machinery fundamental for completion of its lytic life cycle. SEP1 infection and replication process highlights its potential clinical interest targeting stationary phase cells. Abstract : Description of a phage with the ability to initiate its lytic cycle immediately after infecting S. epidermidis stationary cultures assessed by flow cytometry and qPCR.